HISTOLOGICAL AND BIOCHEMICAL EFFECTS OF ARTEETHERTM ON THE LIVER OF WISTAR RATS - Okunlola, A. I.; Okunlola, C. K.; Okani, C. O.; Adewole, O. S.; Ojo, S. K.; Abiodun, A. A.; Bejide, R. A.; Ojewole, J. A. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
ArteetherTM is among the recent drugs that are used to combat choroquine-resistant malarial parasites. This study examined the effects of arteetherTM on enzyme biomarkers of the liver, serum protein concentrations, and liver morphology. Twenty (20) adult albino Wistar rats weighing 200 – 250 g were randomly divided into four groups (A, B, C and D) of five animals each, and used in this study. Group A rats were given intramuscular (i. m.) arteetherTM (3 mg/kg b. w.) daily for 3 days. Group B rats received i. m. arteetherTM (6 mg/kg b. w.) daily for 3 days. Group C rats were given i. m. arteetherTM (3 mg/kg b. w.) daily for 3 days. The same dose was repeated at two-weekly intervals for 4 further weeks, while group D rats which received normal saline (0.9 % w/ v, 3 ml/kg b.w.), served as controls. At the end of the experiment, the body weights of the animals were determined and recorded. Serum levels of alanine transaminase (ALT), aspartate transaminase (ASP), alkaline phosphatase (ALP), total protein (TP) and albumin were assayed, and histological studies were performed. Results obtained show no significant difference (P<0.05) in liver enzymes (ALT, ASP, ALP). TP and albumin were significantly reduced in group C rats. Histological studies revealed no cyto-architectural changes. It is concluded that at therapeutic doses, arteetherTM is well tolerated in Wistar rats. .